126k views
3 votes
The sides of an isosceles triangle are (2x + 1), (2x + 1) and (2x + 4). Treating the longest side as the base, determine an expression for the perpendicular height of the triangle. Give your answer in simplest form.

User Sdoxsee
by
5.2k points

1 Answer

2 votes

Drawing a diagram of the triangle we have

Let a be the length of the perpendicular height of the triangle, then we can solve it using the Pythagorean Theorem


\begin{gathered} a^2+b^2=c^2 \\ a^2+((2x+4)/(2))^2=(2x+1)^2 \\ a^2+(x+2)^2=(2x+1)^2 \\ a^2+x^2+4x+4=4x^2+4x+1 \\ a^2=4x^2+4x+1-x^2-4x-4 \\ a^2=3x^2-3 \\ √(a^2)=√(3x^2-3) \\ \end{gathered}

Therefore, the length of the perpendicular height of the triangle can be given in the expression


√(3x^2-3)

The sides of an isosceles triangle are (2x + 1), (2x + 1) and (2x + 4). Treating the-example-1
User NewTech Lover
by
5.8k points